PO 118 - Anaesthetic Management of a Patient with Friedrich’s Ataxia - Tiago, Catarina; Dias-Vaz, Marta; Marques, Ana; Barata, Melanie; Barreto, Carla (Journal of the Portuguese Society of Anesthesiology, 2023)
x